Peningkatan Literasi Digital Siswa Melalui Pelatihan Desain Poster Mading Menggunakan Canva di Madrasah Ibtidaiyah Jamiatul Khair Tangerang - Fajar Rahayu; Andhika Octa Indarso; Noor Falih; Ridwan Raafi'udin; Sri Mulyantini (Jurnal Pengabdian kepada Masyarakat Bidang Ilmu Komputer, 2025)
The rapid development of digital technology necessitates the enhancement of digital literacy from an early age, including the effective use of digital media as a tool for learning and information communication. This community service activity aimed to improve the digital literacy of students at Jami’atul Khair Islamic Elementary School, Tangerang, through wall magazine poster design training using the Canva application. The implementation method comprised needs identification, delivery of basic design theory and an introduction to Canva, application usage demonstrations, independent practice, and activity evaluation. The evaluation was conducted using questionnaires to assess participants’ levels of understanding, perceptions of the instructional methods, and the benefits of the activity. The results indicated that the majority of participants responded positively to both the training materials and the implementation process, and were able to produce digital wall magazine poster designs that adhered to basic design principles. This activity proved effective in enhancing students’ design skills, creativity, and productive use of digital technology within the school environment. The training is expected to serve as an applicable and sustainable digital literacy activity model for other Islamic elementary school students.